2008
DOI: 10.1021/nl801506w
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Interference in Radial Heterostructure Nanowires

Abstract: Core/shell heterostructure nanowires are one of the most interesting mesoscopic systems potentially suitable for the study of quantum interference phenomena. Here, we report on experimental observations of both the Aharonov-Bohm (h/e) and the Altshuler-Aronov-Spivak (h/2e) oscillations in radial core/shell (In2O3/InOx) heterostructure nanowires. For a long channel device with a length-to-width ratio of about 33, the magnetoresistance curves at low temperatures exhibited a crossover from low-field h/2e oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…In tubular wires, such as carbon nanotubes, and InN nanowires in which only surface electrons conduct, 45 and radial core-shell InO nanowires, 46 the tubular topology of the electron system can be taken into account by periodic boundary conditions. In the following, we focus on wires where the dominant SO coupling is of Rashba type.…”
Section: Tubular Wiresmentioning
confidence: 99%
“…In tubular wires, such as carbon nanotubes, and InN nanowires in which only surface electrons conduct, 45 and radial core-shell InO nanowires, 46 the tubular topology of the electron system can be taken into account by periodic boundary conditions. In the following, we focus on wires where the dominant SO coupling is of Rashba type.…”
Section: Tubular Wiresmentioning
confidence: 99%
“…In particular, an axial field may lead to Aharonov-Bohm (AB) field-periodic modulation of the electron energy spectrum [11] and, if the phase-coherent length exceeds the perimeter of the NW, the observation of magnetoconductance oscillations [12,13]. Indeed, several observations of AB-like oscillations in magnetotransport experiments performed on radial heterostructures have been reported [14][15][16][17][18]. Recently, Gül et al [16] observed fluxperiodic magnetoconductance oscillations in GaAs/InAs coreshell NWs.…”
Section: Introductionmentioning
confidence: 99%
“…When the ON state was switched back to the OFF state by a positive voltage pulse applied at an amplitude of + 2.0 V, this OFF state was sustained even after 390 s with little degradation. Conversely, in the case of shorter alkyl chains (3 a), the retention time was reduced to near 200 s. For the application of MMNVM, the retention time of Ru complex 3 b remained sufficiently large compared with that of DRAM (a few milliseconds), and, furthermore, the retention time of 3 b could be extended to several days by utilizing a nanowire as a channel, [21] as shown in our previous report with 2 a. [22] In addition, the ratio between the probe currents corresponded to the ON/OFF ratio obtained in the I-V characteristics, as depicted in Figure 2.…”
mentioning
confidence: 99%